DECOLONIAL ECOLINGUISTICS IN THE ORAL TRADITION OF SEBLANG AS A FORM OF OSING PEOPLE’S RESISTANCE - Muhammad Fauzi Al Hamidi; Sri Wahyuni; Dyah Werdiningsih; Hasan Busri (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2025)
As global environmental crises continue to grow, greater attention to indigenous ecological knowledge is urgently needed. This study explores the ecological narratives embedded in the oral tradition of Gending Seblang Olehsari within the Osing community, Banyuwangi, East Java Province, Indonesia, through a decolonial ecolinguistic perspective, and examines its role as cultural resistance against hegemonic environmental discourse. In positioning this study within contemporary ecolinguistic and decolonial scholarship, the research emphasizes the urgency of recovering marginalized ecological epistemologies that have been systematically silenced by colonial and modern development paradigms. Employing qualitative methods, the research analyzes oral texts, engages in participatory observation of rituals, and conducts in-depth interviews with community leaders. This methodological design allows the study to capture not only linguistic structures, but also the socio-cultural, historical, and cosmological dimensions through which environmental meaning is produced and sustained in everyday community practices. The findings demonstrate that Gending Seblang embodies ecological symbols, such as kembang gadhung (toxic flower) and ombak umbul (ocean wave), which reflect the Osing cosmology of harmonious and sustainable human–nature relations. These symbols operate as ecological signifiers that encode ethical principles of restraint, reciprocity, and interdependence between human and non-human life forms, offering an alternative worldview to anthropocentric environmental models. Metaphors including Seblang Lukinta (trance upon nature’s bed) and Layar Kumendhung (critique of ecological colonialism) function as linguistic strategies to preserve local knowledge while resisting exploitative Western logic. Through these metaphors, the Osing people articulate a counter-narrative that challenges the reduction of nature into mere economic resources and reasserts indigenous cosmology as a valid and authoritative system of ecological knowledge. The study concludes that this oral tradition is not merely intangible cultural heritage, but a living knowledge system significant for ecological decolonization movements. As such, Gending Seblang should be understood as an active site of epistemic resistance that continues to shape community identity, environmental ethics, and political consciousness.These insights provide a new perspective on integrating local wisdom into environmental policy and sustainability education. Ultimately, this research demonstrates that the preservation of oral traditions is inseparable from the pursuit of ecological justice, particularly in the context of accelerating environmental crises and the enduring legacy of colonial environmental governance.